Identifikasi Spesies Kutu Daun (Hemiptera: Aphididae) pada tanaman jagung (Zea mays L.) di Kabupaten Lamongan - Sholikha, Annida Nur Rifatus; Megasari, Dita; Windriyanti, Wiwin (BIOEDUSCIENCE, 2025)
Background: Aphids are a significant pest in cultivated plants. One crop that is susceptible to aphid infestation is corn. Aphids can cause damage to plants and become vectors of plant viruses. Information on the presence and species of aphids on corn plants in Lamongan Regency has never been reported. The purpose of this study was to determine the species of aphids that attack corn plants in Lamongan Regency. Methods: This research was conducted from May 2024 to July 2024 in 9 maize fields in Lamongan Regency. The method used in this study was the survey method. Corn plants were randomly selected, and sampling was done once in each field. Samples obtained were identified at the Plant Pests and Diseases Laboratory of the UPN “Veteran” Jawa Timur. Results: The aphids identified from 9 fields in Lamongan District consisted of 2 species belonging to the order Hemiptera family Aphididae subfamily Aphidinae and tribe Aphidini. Conclusions: 2 species of aphids were found in 9 corn fields, namely the species R. maidis and H. setariae. The population of R. maidis was found in greater numbers than that of H. setariae.